Immunometabolic Regulations Mediated by Coinhibitory Receptors and Their Impact on T Cell Immune Responses - Patsoukis, Nikolaos; Weaver, Jessica D.; Strauss, Laura; Herbel, Christoph; Seth, Pankaj; Boussiotis, Vassiliki A. (Frontiers in Immunology, 2017)
Host immunity provides wide spectrum protection that serves to eradicate pathogens and cancer cells, while maintaining self-tolerance and immunological homeostasis. Ligation of the T cell receptor (TCR) by antigen activates signaling pathways that coordinately induce aerobic glycolysis, mitochondrial activity, anabolic metabolism, and T effector cell differentiation. Activation of PI3K, Akt and mTOR triggers the switch to anabolic metabolism by inducing transcription factors such as Myc and HIF1, and the glucose transporter Glut1, which is pivotal for the increase of glucose uptake after T cell activation. Activation of MAPK signaling is required for glucose and glutamine utilization, whereas activation of AMPK is critical for energy balance and metabolic fitness of T effector and memory cells. Coinhibitory receptors target TCR proximal signaling and generation of second messengers. Imbalanced activation of such signaling pathways leads to diminished rates of aerobic glycolysis and impaired mitochondrial function resulting in defective anabolic metabolism and altered T cell differentiation. The coinhibitory receptors mediate distinct and synergistic effects on the activation of signaling pathways thereby modifying metabolic programs of activated T cells and resulting in altered immune functions. Understanding and therapeutic targeting of metabolic programs impacted by coinhibitory receptors might have significant clinical implications for the treatment of chronic infections, cancer, and autoimmune diseases.